The Threshold of Democracy : Athens in 403 B.C. - Ober, Josiah; Norman, Naomi J.; Carnes, Mark C. (Mark Christopher), 1950- (New York : W.W. Norton & Company, 2016)
"In this updated addition to the Reacting to the Past family, the classroom is transformed into 5th-century Athens, a city divided in the wake of military defeat and open rebellion. With democratic stability uncertain, students must draw from a wide range of perspectives and original source material to approach issues of citizenship, elections, re-militarization, and dissent. Students also engage directly with history through innovative role-playing games, devised by acclaimed pedagogical experts, which develop leadership, speaking, writing, and critical thinking skills in a fun and unique classroom experience"--
Introduction -- Historical background -- The game -- Roles and factions -- Core texts.
Includes bibliographical references.
Keywords: Democracy -- Greece -- Athens -- History -- To 1500.; Athens (Greece) -- Politics and government